Importância do agroextrativismo para o desenvolvimento das comunidades quilombolas do Amapá - (:unkn) unknown (Brasil, 2023)
This work has as objective, analyze through a bibliographical review the role of agroextractivism in the development of communities remnants of quilombo in the state of Amapá. This is a qualitative bibliographical review. The results were discussed based on studies carried out in remaining territories of quilombos from the state of Amapá. Quilombo Tapereira, Quilombo do Curiaú, Quilombo do Rosa and Quilombo Mel da Pedreira were evaluated. In Amapá, the importance of agroextractivism occurs mainly through food with the sale of surpluses on a small scale. Finally, it was possible to identify that the extractive practice together with agriculture are viable activities for the investigated quilombola communities investigated and contributes to the economy and food sovereignty of the remaining.
Keywords: Extrativismo vegetal, economia, quilombo; CNPQ::CIENCIAS AGRARIAS